Re‐phrasing the question: A simple tool for evaluation of adherence to therapy in patients with inflammatory bowel disease. Issue 6 (1st October 2017) - Engel, T; Ungar, B; Ben‐Haim, G; Levhar, N; Eliakim, R; Ben‐Horin, S
Abstract : Background: Non‐adherence to medication in patients with inflammatory bowel disease (IBD) is a challenging problem which is often overlooked or under‐estimated by the physician or denied by the patient. We aimed to examine if re‐phrasing the wording of the question used by the physician could help in revealing more patients who are non‐adherent, and for whom appropriate counseling may be instituted. Methods: A cross‐sectional questionnaire‐based study of IBD patients treated in a tertiary center was conducted. Patients received a questionnaire detailing their treatments and disease course, as well as their perceptions about disease. Two forms of questions about adherence were deliberately placed in two separate parts of the questionnaire: One was 'are you taking your medications regularly as prescribed?' (Standard question), and the second, more emphatic question, was 'how often does it happen that you miss a drug dosing?' (Re‐phrased question). The rate of non‐adherence disclosed by each of these questions was compared. Sensitivity, specificity and predicative values were computed for each question against the conventional definition of non‐adherence as taking of less than 80% of prescribed medication doses disclosed by any of the methods. Predictors of non‐compliance and of denying non‐compliance were also explored. Results: Overall, 165 patients were included (49% female, mean age 33.7 ± 12.7 SD, median age 30 years, 29.6% with ulcerative colitis, 62.4% with Crohn's disease). Upon questioning, 50 (30.3%) of the patients admitted to non‐adherence in the last month when asked by the emphatic re‐phrased question format, compared with only 10 patients (6%) reporting non‐adherence when asked directly by the standard question (OR 7.4, 95%CI 3.6–15.2, p  < 0.001). Thus, a 'Do you take your medicine regularly' question format disclosed only 20% of genuinely non‐compliant patients and had 16% sensitivity and 98.2% specificity for revealing non‐adherence (PPV 80%, NPV 72.9%) compared with the reference re‐phrased question. The leading cause for non‐adherence was skepticism about drug efficacy or safety (20.5%), followed by vacation or weekend (15%), problems with prescription or pharmacy (13.5%) and forgetfulness (10%). No single demographic or clinical factor correlated with non‐adherence. The only factor which correlated with higher probability for non‐adherence was biological and combination treatment. Conclusion: Non‐compliance with treatment is much more common than patients admit. Asking patients how often does it happen that they miss a drug dosing is a simple, practical tool which performs significantly better in disclosing non‐adherence compared with asking patients if they take their medication as they should.